Low Carb High Protein Diets to Treat Insulin Resistance in Patients with Obesity and/or Type 2 Diabetes Mellitus - Elisabeth Govers (Current Overview on Disease and Health Vol. 7, 2023)
Low carbohydrate, high protein diets have been prescribed since 1797 and are taken seriously by many researchers and health professionals, though the diet is still met with skepticism in mainstream dietetics and medicine. Insulin resistance (IR) is caused by a series of physiological events that begin with hyperfagia and progress to a positive energy balance and weight gain. Because of their high insulin levels, patients with IR gain weight easily and have difficulty losing weight on diets with a normal carbohydrate content. A diet for patients with IR must therefore tackle this problem to make weight loss possible. Recently, developments in the management of type 2 diabetes mellitus incline towards lowering of carbohydrate intakes to put T2DM in remission, making it even more important to look carefully at the evidence, because patients may benefit from it in a direct way. This review discusses the evidence on the diet’s short and long-term effects, effects on comorbidities, and differences from the Mediterranean diet. A search was carried out in Pubmed for articles of obesity management, IR, low carb/high protein diets and weight loss combined with comorbidities, several nutrients and the Mediterranean diet between 1995 and July 2017. In weight loss management, the outcomes were compared to patient observations from dietary practice. Waist circumference measurement makes diagnosis simple. The diet should be low in carbohydrates and rich in protein without inducing ketosis; each person’s needs for energy and macronutrients should be considered. Focusing on unsaturated fats, fat is neither too high nor excessively low. Magnesium, iodine, and vitamin D intake must be at recommended levels. Alcohol consumption is not included in the diet’s initial phase. Exercise is a crucial component of treatment because it builds endurance and resistance. Patients taking type 2 diabetes medication need to carefully monitor their food and glucose levels. Low carbohydrate/high protein diets should be considered as a serious treatment option for all obese patients with and without comorbidities. They should be administered by specialized dietitians as part of a multidisciplinary team. Low carbohydrate/high protein diets should be considered as a serious treatment option for all obese patients with and without comorbidities. They should be administered by specialised dietitians working in a multi-disciplinary team.